Comparative impact of drought stress on growth and yield traits of riceberry and KDML105 rice varieties - Sehawong, W.; Subepang, S.; Kaewtaphan, P.; Chotchutima, S. (International Journal of Agricultural Technology, 2025)
The impact of drought stress on the growth and yield components of two Thai rice varieties, Riceberry and KDML 105, was investigated under four irrigation levels (1,000, 3,000, 5,000, and 7,000 mL per 10 days). Significant differences were observed between the two varieties across multiple traits. KDML 105 exhibited superior stem height, dry matter accumulation, and grain production, particularly under high water availability. In contrast, Riceberry produced a greater number of tillers per hill and retained higher soil moisture under limited irrigation, indicating improved water use efficiency (WUE). While KDML 105 achieved optimal grain production and seed weight at 7,000 mL, Riceberry demonstrated superior adaptability to water-limited conditions, due to its compact morphology and effective water retention. These findings suggested that KDML 105 is better suited for water-abundant environments, whereas Riceberry is a promising variety for drought-prone areas requiring water-saving cultivation practices.